2015
DOI: 10.1111/ijcp.12588
|View full text |Cite
|
Sign up to set email alerts
|

Admission blood pressure and 1-year mortality in acute myocardial infarction

Abstract: In acute myocardial infarction, admission blood pressure predicts long-term mortality in an inverse relation. With increasing admission blood pressure long-term mortality decreases. Low admission blood pressure should serve as a warning sign in patients with AMI. Admission blood pressure should therefore be interpreted in opposite to the regular, preventive, point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Excessive vasopressor use may lead to increased afterload and increased oxygen consumption of the heart, thereby aggravating the myocardial damage. On the other hand, hypotension or even low-normal blood pressure at hospital admission is associated with increased mortality in patients with acute myocardial infarction [ 22 ]. In addition, hypotension can decrease coronary perfusion pressure leading to myocardial hypoperfusion and ischaemia and, eventually, cardiovascular collapse [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive vasopressor use may lead to increased afterload and increased oxygen consumption of the heart, thereby aggravating the myocardial damage. On the other hand, hypotension or even low-normal blood pressure at hospital admission is associated with increased mortality in patients with acute myocardial infarction [ 22 ]. In addition, hypotension can decrease coronary perfusion pressure leading to myocardial hypoperfusion and ischaemia and, eventually, cardiovascular collapse [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[13] The results of a prospective multicenter observational study on 11,292 Korean patients with STEMI found that those with normal SBP (100-139 mmHg) had a higher risk of in-hospital mortality compared with hypertension patients, but not of all-cause death or MACE. [15] Another study on 3943 patients with acute MI reached a similar conclusion [12]. In addition, using data from more than 10,000 non-ST-elevation ACS patients in two large registries, Lee et al found an independent relationship between lower SBP and in-hospital mortality; hypertension history or use of antihypertensive medication did not affect these associations [14].…”
Section: Plos Onementioning
confidence: 84%
“…[8][9][10][11] Additionally, several studies have previously demonstrated the inverse link between increasing admission SBP and the risk of adverse cardiovascular outcome. [12][13][14][15] However, there is a lack of further investigation into the nonlinear relationship between admission SBP and adverse outcome of AMI patients.…”
Section: Introductionmentioning
confidence: 99%
“…A 70% relative risk reduction for mortality in the highest vs the lowest BP category was documented. Regarding diastolic BP, levels <60 mm Hg were associated with a worse outcome …”
Section: Admission Blood Pressure and Patient Outcome In Acute Coronamentioning
confidence: 97%